Variation in Rumen Bacteria of Lacaune Dairy Ewes From One Week to the Next - Fresco, Solène; Marie-Etancelin, Christel; Meynadier, Annabelle; Martinez Boggio, Guillermo (Frontiers in Microbiology, 2022)
Bacteria are the most abundant microorganisms in the rumen microbiota and play essential roles mainly through fermentation of vegetal compounds that produce fatty acids. In this study, we aimed to assess bacterial composition stability over a 1-week period and the stability of its relationships with fatty acid phenotypes. The study was performed using 118 Lacaune dairy ewes from the INRAE Experimental Unit of La Fage. Rumen and milk samples were obtained twice, 1 week apart, from the ewes to analyze microbiota, volatile fatty acids, and long-chain fatty acid compositions. Bacterial composition was assessed using 16S rRNA gene sequencing, and compositional data principles were applied to the microbiota and fatty acids. Bacterial composition differed between the two weeks of sampling, characterized by different proportions of the two main phyla, Bcateroidetes and Firmicutes. The repeatability of the operational taxonomic units (OTUs) was low, although it varied significantly. However, 66 of them presented a repeatability of over 0.50, and were particularly associated with fatty acid phenotypes. Even though the OTUs from the same bacterial families presented similar correlations to fatty acids in both weeks, only a few OTUs were conserved over the two weeks. Further studies are required to elucidate the effects modifying the bacterial composition over 1 week and the specificities of the highly repeatable OTUs.